Factors Associated With Feeling Ashamed of Disclosure of HIV‐Positive Status Among Women Who Self‐Reported to Health Facilities for HIV Testing in Kenya: Analysis of 2022 Kenya Demographic and Health Survey - Isaac Isiko; Kelly Taremwa; Simon Nyegenye; Aaron Mwesigwa; Reagan Muwanga Mutebi; Lenz Nwachinemere Okoro; Eneh Nchiek Edet; Catherine Chepkoskei Koech; Naya Gadzama Bulus; Jackson Micheal Asingwire (Health Science Reports)
ABSTRACT Background This study aimed to determine the factors associated with feeling ashamed of disclosing HIV‐positive status among females who self‐reported to health facilities for HIV testing in Kenya. Method This study used the Kenya Demographic Health Survey data set for 2022. A total of 18,506 women aged 15–49 years were selected from the sample clusters; 13,815 had ever tested for HIV and 332 had positive results for HIV. The chi‐squared test was applied to determine the association between the selected variables of interest and the outcome variable. Furthermore, to identify the explanatory variables that were associated with the outcome variable of interest, logistic binary regression was performed. A p > 0.05 and all statistical analyses were conducted using Microsoft Excel (xlsx) and STATA15. Results The analysis included 332 women who had tested positive during the survey out of which 125(38%) women agreed to have felt ashamed to disclose their HIV+ status. Agreed to stigma (AOR = 1.92, 95% CI: 1.15, 3.22; p < 0.05) and being intimidated by health workers (AOR = 2.49, 95% CI: 1.05, 5.93; p < 0.05) were significantly associated with feeling ashamed of disclosing HIV+ status. The remaining variables, such as age category, residence, marital status, educational attainment, total number of children born, access to information, sex partners excluding spouses in the last 12 months, and number of lifetime sex partners, were not associated with feeling ashamed. Conclusion Health stigmatization and intimidation Stigmatization had an almost two‐fold likelihood of causing shame in the disclosure of HIV status among females with HIV who were studied.